Accumulation and release potential of soil phosphorus in residential areas of Hangzhou city, China - ZHANG Ming-kui; FU Juan-lin; LI Ren-an (浙江大学学报. 农业与生命科学版)
Accumulation of phosphorus in soils increases the potential of P run off from the soils and thus affects environmental quality. In this study forty-nine soil samples from different residential areas in Hangzhou city, Zhejiang province were collected for analyzing forms and saturation degree of P, and investigating the accumulation and release potential of P in the soils. The Hedley fractionation scheme was used to divide soil P into water-soluble, NaHCO3-soluble, NaOH-soluble, HCl-soluble and residual P. The results showed that soils of the residential areas in the city had been enriched with P to a great extent, mean total soil P in the residential areas was twice of that in agricultural land. About 86% of the residential soils had water soluble P higher than 10 mg/kg, and 59% of the soils had P saturation degree greater than 25%, an environmentally sensitive threshold. The soil P was mainly composed of HCl-P which accounted for 50%-60% of the total P. Most of the P (80%) in the soils could be extracted by water, NaHCO3, NaOH and HCl. The accumulation and release potential of P in the soils increased with age increasing of the residential areas. It is suggested that soil may impose a significant negative influence on environment when its total P content exceeds 1.2 g/kg.